2010
DOI: 10.4049/jimmunol.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: PulmonaryLegionella pneumophilaIs Controlled by Plasmacytoid Dendritic Cells but Not Type I IFN

Abstract: Plasmacytoid dendritic cells (pDCs) are well known as the major cell type that secretes type I IFN in response to viral infections. Their role in combating other classes of infectious organisms, including bacteria, and their mechanisms of action are poorly understood. We have found that pDCs play a significant role in the acute response to the intracellular bacterial pathogen Legionella pneumophila. pDCs were rapidly recruited to the lungs of L. pneumophila-infected mice, and depletion of pDCs resulted in incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
0
37
0
1
Order By: Relevance
“…Furthermore, type I IFN-␣ receptor-deficient (IFNAR Ϫ/Ϫ ) macrophages were more permissive to L. pneumophila infection in vitro than were wild-type cells (11). There was no difference in bacterial detection in the lungs when IFNAR2 Ϫ/Ϫ and wild-type mice were compared 48 h after L. pneumophila infection (12), nor was there a difference in lung bacterial burden between wild-type and IFNAR Ϫ/Ϫ mice (13). Despite this, most reports suggest that type I IFN supports cellular resistance to L. pneumophila infection.…”
mentioning
confidence: 91%
“…Furthermore, type I IFN-␣ receptor-deficient (IFNAR Ϫ/Ϫ ) macrophages were more permissive to L. pneumophila infection in vitro than were wild-type cells (11). There was no difference in bacterial detection in the lungs when IFNAR2 Ϫ/Ϫ and wild-type mice were compared 48 h after L. pneumophila infection (12), nor was there a difference in lung bacterial burden between wild-type and IFNAR Ϫ/Ϫ mice (13). Despite this, most reports suggest that type I IFN supports cellular resistance to L. pneumophila infection.…”
mentioning
confidence: 91%
“…Whether L. pneumophila can survive within neutrophils and translocate T4SS effectors into these cells during pulmonary infection is unknown. L. pneumophila can be taken up by a wide variety of cell types in vitro, such as neutrophils, bone marrow-derived dendritic cells, type I and type II alveolar epithelial cells, endothelial cells, and plasmacytoid dendritic cells (35)(36)(37)(38)(39). However, the efficiency of L. pneumophila replication within these cell types varies greatly, and whether these cell types are injected by the T4SS or productively infected in vivo is unknown.…”
mentioning
confidence: 99%
“…Similarly to macrophages, dendritic cells (including plasmocytoid dendritic cells) are recruited in the early stages of Legionella infection in mice [9]. Although able to phagocytose Legionella, in vivo infections in mice have demonstrated that dendritic cells contain only a few bacteria at a time.…”
Section: Legionella Infection In Other Immune Cellsmentioning
confidence: 99%
“…Within the lungs, Legionella are phagocytosed by resident alveolar macrophages [8] and, in mice, by recruited dendritic cells [9]. Macrophages are specialized phagocytes capable of engulfing whole cells destined for destruction within hydrolytic lysosomes, called phagolysosomes.…”
mentioning
confidence: 99%